2017
DOI: 10.5194/acp-2016-1104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of Central-African aerosol and trace-gas emissions based on MAX-DOAS measurements and model simulations over Bujumbura, Burundi

Abstract: Abstract.We present MAX-DOAS measurements of NO 2 , HCHO, and aerosols performed in Central Africa, in the city of Bujumbura, Burundi (3.38 Aerosol-extinction and trace-gas vertical profiles are retrieved by applying the optimal-estimation-based profiling tool bePRO to the measured O 4 , NO 2 and HCHO slant-column densities. The MAX-DOAS vertical columns and profiles are used for 5 investigating the diurnal and seasonal cycles of NO 2 , HCHO, and aerosols. Regarding the aerosols, the retrieved AODs are compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

7
1

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Bujumbura is located in tropical Africa that is typically affected by the biomass burning emissions, mainly during the local dry seasons (June-August and January-February), and to a lesser extend, by the anthropogenic emissions, throughout the year with negligible seasonal variations. The single scattering albedo in Bujumbura is higher in March-May (∼0.9), related to the major rain season, and lower in July-August and December-January (0.83-0.87), coinciding with the intensive agricultural activities and transport of forest fire emissions in the surrounding regions (Gielen et al, 2017). The asymmetry parameter is on average 0.69, in agreement with values in biomass burning aerosol models (Torres et al, 2013).…”
Section: Implicit Aerosol Correction 15supporting
confidence: 76%
See 2 more Smart Citations
“…Bujumbura is located in tropical Africa that is typically affected by the biomass burning emissions, mainly during the local dry seasons (June-August and January-February), and to a lesser extend, by the anthropogenic emissions, throughout the year with negligible seasonal variations. The single scattering albedo in Bujumbura is higher in March-May (∼0.9), related to the major rain season, and lower in July-August and December-January (0.83-0.87), coinciding with the intensive agricultural activities and transport of forest fire emissions in the surrounding regions (Gielen et al, 2017). The asymmetry parameter is on average 0.69, in agreement with values in biomass burning aerosol models (Torres et al, 2013).…”
Section: Implicit Aerosol Correction 15supporting
confidence: 76%
“…Therefore, we assume that the thin clouds near the surface from the OCRA/ROCINN cloud products are attributed to aerosol loads for measurements with cloud radiance fraction < 0.5 or cloud fraction < 0.2, and we evaluate the accuracy of implicit aerosol correction by comparing it with explicit aerosol correction. For that purpose, the explicit correction for aerosols is implemented using ground-based aerosol observations in Xianghe (39.75 • N, 116.96 • E), which is a suburban site surrounded by heavily industrialized areas in northeastern China (Clémer et al, 2010;Hendrick et al, 2014;Vlemmix et al, 2015), and in Bujumbura (3.38 • S, 29.3 • E), which is located in the Central African country of Burundi with intensive biomass burning activities in the surroundings (Gielen et al, 2017), as indicated in Fig. 14 and 15, respectively.…”
Section: Implicit Aerosol Correction 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite data display a negative bias against ground-based reference data at all stations, except Reunion Island and UHMT-Houston, which are both coastal sites, highly heterogeneous in nature (Tzortziou et al, 2014;Loughner et al 2014;Martins et al, 2016). Negative biases of about -80% are observed in Bujumbura and Nairobi, 5 which can be related to the small NO2 signal and the localized nature of the sources at these sites, combined with a complex orography (Gielen et al, 2017;Compernolle et al, 2020). Systematic uncertainties in the estimation of the stratospheric column in satellite datasets could also contribute to the observed underestimation, considering the overall small tropospheric NO2 signals at these locations.…”
Section: Comparison Of Ground-based and Satellite Datasetsmentioning
confidence: 97%
“…These differences are the result of the different chemical mechanism, transport scheme, and emission inventory employed by the model, the different spatial resolution, and the use of daily vs. monthly profiles. In TM5-MP, the use of an updated NO x emissions from the MACCity inventory (Granier et al, 2011) produces more realistic profiles. Improvement in the spatial resolution gives a more accurate description of the NO 2 gradient and transport.…”
Section: A Priori Vertical Profilesmentioning
confidence: 99%